Semantics : a coursebook - Hurford, James R., Ph.D.; Heasley, Brendan., Ph.D.; Lê Hiền Thảo, M.A.; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2001)
Basic ideas in semantics; From reference; To sense; Logic; Word meaning; Interpersonal meaning.
Keywords: English language; Linguistics; Semantics; Semantics